Pemberdayaan Ekonomi Masyarakat Melalui Budidaya Tanaman Sayuran - Kurniawati Mulyanti; Supandi Supandi (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The implementation of Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar) carried out by the government in the context of controlling the transmission of the Corona Virus -19 disease has an impact on the decline in the level of welfare of the Indonesian people. A real program is needed through community empowerment to improve the community's economy, one of which is through the cultivation of vegetables. This community service activity program aims to save expenses, especially household expenses and increase people's income during the COVID-19 pandemic. In addition, by cultivating vegetable crops, the environment becomes cleaner, neater and greener. The socialization of the activities was carried out using the lecture method and the practice of planting vegetables. The implementation of the activities of the community empowerment program through vegetable cultivation was carried out in the Bojong Menteng Village, Rawa Lumbu District. The enthusiasm of the community is shown by the community's participation in the activities of this empowerment program. as many as 42 representatives from Rt participated in the activities of this program. Keyword: Community Economic Empowerment, Vegetable Cultivation